Financial market risks and the hedging powers of unconventional assets under different conditions - Idris A. Adediran; Olajide O. Oyadeyi; Olayode W. Agboola; Kofoworola H. Raji; Habeeb F. Ayoade (Journal of Applied Economics)
The global financial ecosystem has become increasingly precarious for investors in the face of diverse risks such as macroeconomic, policy uncertainty, geopolitical, and systemic risks. This study examines hedging these risks with alternative classes of unconventional assets; clean stocks, precious metals, Shariah-compliant stocks, and REITs, as contribution to the literature that contains fragmented analysis of individual assets or specific risks. The study employs a generalized least squares estimator that carefully eliminates salient econometric problems alongside quantile analysis using daily data spanning 5/17/2010 to 12/16/2024. The striking findings therefrom are: (i) precious metals, especially gold, are the best hedging candidates except against geopolitical risk where clean stocks come in to provide cover; (ii) analyses of quantiles provide fresh insights that indicate that most of the hedging powers of the assets are found during bearish market condition. The study accentuates the use of gold for portfolio diversification and for keeping foreign reserves.